FENOMENA TERJADINYA KENAKALAN REMAJA - Lilis Karlina (JURNAL EDUKASI NONFORMAL, 2020)
Dolescence is often known as rebellion. At this time, a child who is just experiencing puberty often displays a variety of emotional upheaval, withdrawing from the family, and experiencing many problems, both at home, school, or in the home environment and in the environment of friends. This paper is a literature study from various existing references, then the data is packaged as data and information material that can provide an overview of the condition of juvenile delinquency. The aim is to find out juvenile delinquency, factors that cause juvenile delinquency. Then how the role of parents, schools and society in tackling juvenile delinquency. Therefore, in dealing with juvenile delinquency, there needs to be concrete actions taken by parents, teachers and the community, so that deviant behavior does not occur.